Extension et variété de l’usage du cloisonnement urbain de Makati à Metro-Manila (Philippines) - Catherine Guéguen (Territoire en Mouvement)
Urban partitioning of large cities, especially in developing countries, is one of the major topics in current geographical studies. The case of Metro-Manila is examined in this paper with several approaches. Historically, the progressive enclosing of neighborhoods may be linked with the rapid population growth of the Philippines’ metropolis and the imposition of an external urban model on a poor urban environment. The quest for a pleasant quality of life is also one of the main goals of the residents in any of these walled areas, regardless of their geographical scale. Urban partitioning can also be viewed as an option for urban renewal or a specific model of economic development in this large metropolis, as examplified by the major business center in Makati.